A hybrid model to study the effect of tooth lead modifications on the dynamic behavior of double helical planetary gears. (November 2019) - Portron, Stéphane; Velex, Philippe; Abousleiman, Vincent
In this paper, a hybrid model is used to investigate the dynamic behavior of planetary gears. Sun-gear, planets, and ring-gear are modeled using lumped parameters elements, while planet carrier is integrated via a condensed finite element model. This approach intends to be more precise than the traditional lumped parameter models while keeping acceptable computational times. In some aeronautical applications, tooth lead modifications can be necessary to counterbalance the effect of planet carrier deflections on tooth load distribution. This study focuses on the influence of various lead modifications on the dynamic behavior of double helical planetary gears over a broad range of loads.